2015
DOI: 10.1002/adfm.201504461
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast and Highly Reversible Sodium Storage in Zinc‐Antimony Intermetallic Nanomaterials

Abstract: The progress on sodium-ion battery technology faces many grand challenges, one of which is the considerably lower rate of sodium insertion/deinsertion in electrode materials due to the larger size of sodium (Na) ions and complicated redox reactions compared to the lithium-ion systems. Here, it is demonstrated that sodium ions can be reversibly stored in Zn-Sb intermetallic nanowires at speeds that can exceed 295 nm s −1 . Remarkably, these values are one to three orders of magnitude higher than the sodiation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 56 publications
(62 reference statements)
3
49
0
Order By: Relevance
“…The barriers were relatively low in all these phases, as shown in Table 1. This value is lower than that of NaTiO 2 (≈220 meV), [60] SnO 2 (410 meV), [52] bulk MoS 2 (≈700 meV), [61] and tetragonal NaZnSb (470 meV), [46] consistent with the ultrafast initial Na + ion intercalation speed. This value is lower than that of NaTiO 2 (≈220 meV), [60] SnO 2 (410 meV), [52] bulk MoS 2 (≈700 meV), [61] and tetragonal NaZnSb (470 meV), [46] consistent with the ultrafast initial Na + ion intercalation speed.…”
Section: Sodiation Kinetics and Phase Transformationsupporting
confidence: 62%
See 2 more Smart Citations
“…The barriers were relatively low in all these phases, as shown in Table 1. This value is lower than that of NaTiO 2 (≈220 meV), [60] SnO 2 (410 meV), [52] bulk MoS 2 (≈700 meV), [61] and tetragonal NaZnSb (470 meV), [46] consistent with the ultrafast initial Na + ion intercalation speed. This value is lower than that of NaTiO 2 (≈220 meV), [60] SnO 2 (410 meV), [52] bulk MoS 2 (≈700 meV), [61] and tetragonal NaZnSb (470 meV), [46] consistent with the ultrafast initial Na + ion intercalation speed.…”
Section: Sodiation Kinetics and Phase Transformationsupporting
confidence: 62%
“…The single crystal orthorhombic stibnite in the pristine state (Figure 2d-1) differed from the almost amorphous state of the fully expanded SSNR/C electrode (Figure 2d-2) with two bright diffraction rings which can be indexed to Na 2 O (Fm-3m). [46,51,56,57] No other crystalline phase was found in the fully expanded SSNR/C electrode, indicating an amorphous state of the products. [46,51,56,57] No other crystalline phase was found in the fully expanded SSNR/C electrode, indicating an amorphous state of the products.…”
Section: Morphology Change By In Situ Tem Observationmentioning
confidence: 96%
See 1 more Smart Citation
“…In the latest years, some work reported that Sb-based intermetallic compounds including Fe-Sb, [140][141][142][143] Cu 2 Sb, [144,145] Mo 3 Sb 7 , [146] Zn-Sb, [131,[147][148][149] Bi-Sb alloys [132] are capable of sodium storage due to the metallic nanocrystals formed during Na + intercalation process, which effectively enhance electrical conductivity as well as buffer the expansion stress upon cycling. Specifically, Bi can be alloyed with Sb at any molar ratio because of the similar physiochemical properties with Sb, which will partly solve the problem of shortened plateau in the voltage profile when introducing a second element into the Sb system.…”
Section: Other Antimony-based Anodesmentioning
confidence: 99%
“…ZnSb/C composite was successfully prepared by HEMM [226] ; however, this method was proven to be unsuccessful for milling Zn and Sb alone. [237] In the development of MSb alloys with M being an active element toward Na, bismuth (Bi) has been recently studied by Zhao et al [228] BiSb alloys with different compositions were prepared by HEMM from the metals and acetylene black. Better results were obtained for crystalline Zn 4 Sb 3 films prepared by Jackson et al [227] by electrodeposition.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%